Importance of Medication Knowledge in Patient Safety - Kenneth L Miller (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2017)
Pharmacology is an integral component in a physical therapist professional education as physical therapists play an important role in improving medication safety by being cognizant of the medications a patient is taking and monitoring for medication effects with an emphasis on physical functioning and determining if medications are adversely affecting physical functioning. Physical therapists (PT) encounter many adults that take five or more medications and knowing of the medications and their effects - both intended and undesired allow PT's the opportunity to improve patient safety, reduce the risk of adverse drug events and improve therapist practice. Many medications that appear to be safe are potentially inappropriate for the geriatric population and use of the Beers Criteria including non-steroidal anti-inflammatories that increase the risk of gastro-intestinal bleeding and worsen heart failure. Other medications increase the risk of myopathy and tendinopathy which must be taken into account when designing safe and effective care plans.